Pelatihan Teknik Proyeksi Bisnis Pada Kelompok Usaha Di Desa Kassi Kecamatan Rumbia Kabupaten Jeneponto - Ilma Wulansari Hasdiansa; Sitti Hasbiah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This community service activity aims to increase the understanding and ability of business groups in Kassi Village, Rumbia District, Jeneponto Regency in making effective business projections. This program is expected to provide strategic provision for business actors in managing finances, planning business development, and facing market challenges. The technique of implementing this activity includes three stages starting from the preparation stage, the implementation stage and the activity evaluation stage. The results of the training showed that traditional business owners have difficulty in applying business forecasting techniques to their businesses because sales records are sometimes incomplete or non-existent. After conducting the simulation, participants were able to understand the basis of sales forecasting for future sales forecasts. In addition, business owners can know their business forecast with certainty. Knowledge of business forecasting is expected to improve business performance and competitiveness. The limitation of this training is that the implementation method does not use instructional techniques so that knowledge about business forecasting can be implemented in business activities.